2018
DOI: 10.1186/s12916-018-1170-z
|View full text |Cite
|
Sign up to set email alerts
|

A model of access combining triage with initial management reduced waiting time for community outpatient services: a stepped wedge cluster randomised controlled trial

Abstract: BackgroundLong waiting times are associated with public community outpatient health services. This trial aimed to determine if a new model of care based on evidence-based strategies that improved patient flow in two small pilot trials could be used to reduce waiting time across a variety of services. The key principle of the Specific Timely Appointments for Triage (STAT) model is that patients are booked directly into protected assessment appointments and triage is combined with initial management as an altern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(62 citation statements)
references
References 40 publications
2
59
0
1
Order By: Relevance
“…The perceived advantage of reduced waiting times concurs with the main findings from the stepped wedge cluster randomised controlled trial, which found an average reduction in waiting of 34% (24 days) [12]. In contrast, the perception of an increased wait time to first review appointment is not supported by findings in the trial [12]. While it is possible that there were individual cases where clinicians had difficulty scheduling patients to their first review appointment, there was no difference recorded in the time between the first and second appointment after the STAT model had been implemented across the eight sites.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The perceived advantage of reduced waiting times concurs with the main findings from the stepped wedge cluster randomised controlled trial, which found an average reduction in waiting of 34% (24 days) [12]. In contrast, the perception of an increased wait time to first review appointment is not supported by findings in the trial [12]. While it is possible that there were individual cases where clinicians had difficulty scheduling patients to their first review appointment, there was no difference recorded in the time between the first and second appointment after the STAT model had been implemented across the eight sites.…”
Section: Discussionsupporting
confidence: 79%
“…The perceived advantage of reduced waiting times concurs with the main findings from the stepped wedge cluster randomised controlled trial, which found an average reduction in waiting of 34% (24 days) [12]. In contrast, the perception of an increased wait time to first review appointment is not supported by findings in the trial [12].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Waiting for healthcare services is a problem across the care continuum [1] in emergency departments [2], acute hospitals [3] and in ambulatory, community and outpatient settings [4]. Much work has been done on patient flow particularly in the acute setting [5] but there has been increased attention focusing on access, triage and patient flow in non-bed-based services [68]. As chronic disease management relies on responsive outpatient services, demand and wait lists for these services has increased [8].…”
Section: Introductionmentioning
confidence: 99%